2013
DOI: 10.1212/wnl.0b013e31828cfad0
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant vasovagal syncope

Abstract: Familial VVS, inherited in an autosomal dominant manner, may not be rare and has similar features to sporadic VVS. The chromosome 15q26 locus in family A increases the susceptibility to VVS but does not predispose to a particular vasovagal trigger. Linkage analysis in the remaining families established likely genetic heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Klein et al (52) studied 44 Australian families with a familial history of syncope and identified 6 families with apparent autosomal dominant inheritance. Microsatellite markers identified in the largest family an apparent locus in chromosome locus 15q26, but sequencing of nearby candidate genes did not reveal mutations.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…Klein et al (52) studied 44 Australian families with a familial history of syncope and identified 6 families with apparent autosomal dominant inheritance. Microsatellite markers identified in the largest family an apparent locus in chromosome locus 15q26, but sequencing of nearby candidate genes did not reveal mutations.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…19 The original findings of defective biogenic amine metabolism in a significant proportion of Rett syndrome subjects was confirmed and molecular animal studies utilizing severe and less severe human MeCP2 mutations strongly indicated the role of the MeCP2 gene in controlling neuronal specific genes and/or molecules involved in biogenic amine biosynthesis and related behavioral changes. Given the frequent familial nature of neurocardiogenic syncope and dysautonomia 20 , detailed molecular studies (such as whole exome analysis) will be of considerable interest in our cohort of patients with dysautonomia.…”
Section: Discussionmentioning
confidence: 99%
“…What is the ratio between the different inheritance patterns of VVS? The findings reported in [ 25 ] provide a rough idea of this. Among the 44 multiplex families with VVS examined in [ 25 ], an autosomal dominant inheritance pattern was revealed in 6 families.…”
Section: The Inheritance Pattern Of Vvsmentioning
confidence: 95%
“…The findings reported in [ 25 ] provide a rough idea of this. Among the 44 multiplex families with VVS examined in [ 25 ], an autosomal dominant inheritance pattern was revealed in 6 families. The largest of these families included 30 subjects suffering from VVS in 3 generations; in the remaining 5 families, the number of subjects with VVS ranged from 4 to 14.…”
Section: The Inheritance Pattern Of Vvsmentioning
confidence: 95%